2008
DOI: 10.1177/0013164408315268
|View full text |Cite
|
Sign up to set email alerts
|

Factor Structure of Scores From the Maslach Burnout Inventory

Abstract: This study provides a summary of 45 exploratory and confirmatory factor-analytic studies that examined the internal structure of scores obtained from the Maslach Burnout Inventory (MBI). It highlights characteristics of the studies that account for differences in reporting of the MBI factor structure. This approach includes an examination of the various sample characteristics, forms of the instrument, factor-analytic methods, and the reported factor structure across studies that have attempted to examine the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(89 citation statements)
references
References 69 publications
5
77
0
7
Order By: Relevance
“…Although the correlations between the two other burnout dimensions and personal accomplishment increase when the latter is assessed with negatively worded items (Schaufeli & Salanova, 2007), some have argued that the wording has led to an artificial clustering of the subfactors (Halbesleben & Demerouti, 2005). For instance, an extensive review of 45 factor analytic studies on the MBI demonstrated that besides the original three-factor solution, empirical data have also supported alternative models (i.e., two-, four-, or five-factor solutions and models with a higher order factor; Worley, Vassar, Wheeler, & Barnes, 2008). In addition, previous findings have indicated that exhaustion and cynicism might be considered the core symptoms of burnout, whereas personal accomplishment might instead be interpreted as an antecedent or as a consequence of burnout .…”
Section: Burnout: Definition and Measurementmentioning
confidence: 99%
“…Although the correlations between the two other burnout dimensions and personal accomplishment increase when the latter is assessed with negatively worded items (Schaufeli & Salanova, 2007), some have argued that the wording has led to an artificial clustering of the subfactors (Halbesleben & Demerouti, 2005). For instance, an extensive review of 45 factor analytic studies on the MBI demonstrated that besides the original three-factor solution, empirical data have also supported alternative models (i.e., two-, four-, or five-factor solutions and models with a higher order factor; Worley, Vassar, Wheeler, & Barnes, 2008). In addition, previous findings have indicated that exhaustion and cynicism might be considered the core symptoms of burnout, whereas personal accomplishment might instead be interpreted as an antecedent or as a consequence of burnout .…”
Section: Burnout: Definition and Measurementmentioning
confidence: 99%
“…El notable interés por el estudio del síndrome de burnout se debe a que, como señalan diferentes meta-análisis (Alarcon, 2011;You, Huang, Wang, & Bao, 2015), éste constituye un importante problema social en cualquier ámbito profesional.…”
Section: Introductionunclassified
“…A partir de este modelo tridimensional, los estudios sobre el síndrome en diversos contextos se han incrementado de manera significativa con la finalidad de elaborar modelos explicativos, desarrollar instrumentos que permitan su evaluación y analizar la relación que el síndrome presenta respecto a otras variables (e.g. Harris & Watson, 2014;Worley, Vassar, Wheeler, & Barnes, 2008).…”
Section: Introductionunclassified
“…Conceptually, it is proposed that personal accomplishment is more accurately conceptualized as a personal characteristic rather than a symptom of burnout (23) and empirically previous study findings suggest that personal accomplishment is not strongly related to the emotional exhaustion and depersonalization (24). Developed initially for human service workers, the MBI was found a valid and reliable measure of job burnout across occupations, cultures and languages (4,25,26). In Iran, Ahgar (27) the coefficient of burnout scale and its dimensions of Chronbach's reliability, using the test-retest method reported as follows; job burnout (0.88 and 0.90), emotional exhaustion (and 0.86 0.89), depersonalization (0.84 and 0.86) and individual failure (0.85 and 0.84).…”
Section: Job Burnout Inventorymentioning
confidence: 99%